Effects of International Trade on Economic Growth in Nigeria - Victor, Ameh, Ojonugwa; Nwakwo, Odi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study empirically analyzed the effects of international trade on the economic growth of Nigeria from 1981 to 2020 using the Ordinary Least Squares (OLS) technique. The fundamental factors limiting Nigeria’s trade include the country’s lean production and export base dominated by low value products such as raw materials and primary commodities, very high trade cost, tariff and non- tariff barriers to intra-Nigeria trade. The specific objectives of this study are; to ascertain the effects of exchange rate, trade policy changes and to examine how trade liberalization affects Nigeria’s economic growth. The study was anchored on the theory of comparative cost and the Factor Endowment theory Independent variables such as, policy changes (dummy), exchange rates and liberalization/openness were regressed on real Gross Domestic Product (GDP) of Nigeria using secondary data from Central Bank of Nigeria Statistical Bulletin 2020. The econometric diagnostics for presence of unit roots in the series was conducted using the Augmented Dickey-Fuller technique and the tests indicate that the variables were integrated in order of 1(1). The Johansen co-integration test was conducted in determining the co-integration among the variables in the various equations which confirms the absence of long-run equilibrium. Findings from the study revealed that exchange rates in the country had negative but insignificant relationship with economic growth. However, the several trade policies in Nigeria have been seen to retard growth in economic prosperity of the country’s economy, the impact of which is negative and significant on GDP growth. Economic growth, exports and imports, exchange rate, and Inflation all exhibit long-term co-integration, as determined by a co-integration test. Export positively impacted on growth while inflation and exchange rate were found to be negatively affecting growth in Nigeria. The study indicated that there is a beneficial association between international commerce and economic growth and supports the policy of encouraging exports and expanding Nigeria’s presence on global markets. Consequently, the study recommends that, federal government of Nigeria should embark on programmes and policies to promote local production and discourage importation of certain essential products for trade to have the desired impact on the growth of Nigeria’s economy.